Effect Study of Aperture Distribution on the Capillary Pressure-Saturation Relation for the Single Fracture. (8th November 2017) - Wang, Yuan; Wu, Chenglong; Zhou, Yuntian
Abstract : A systematic numerical method was presented to investigate the effect of aperture distribution on the relation of capillary pressure versus fluid saturation (P-S relation) for a single fracture. The fracture was conceptualized as a two-dimensional lattice-grid model and its aperture field was described by a probability distribution. Based on the invasion percolation theory, a program was developed to simulate the quasi-static displacement. The simulation was verified validly by comparisons of the experimental results. The effects of the statistical parameters were further quantified. The results show that the largest local aperture on the fracture boundary determines the AEV. The larger mean decreases the variation coefficient, which causes the more uniform aperture field, smoother air invasion front, and steeper capillary pressure-saturation curve (CPSC). The larger standard deviation increases not only the range but also the contrast degree of the apertures, thus providing a nondeterministic rule in the P-S relation. The larger correlation length causes a more homogeneous aperture field and a dual connectivity of the fracture. The increase of the difference and contrast degree between the small and large apertures results in dual-aperture fields. The dual-aperture field and dual connectivity of the fracture both contribute to the bimodal characteristic of the CPSC.